Response and point of no return (PNR) of penaeid shrimp under artificial cold treatment - Huq, K A; Molla, M F A; Islam, M Aminul; Hossain, M A (Indian Journal of Fisheries, 2011)
For easy handling and transportation of live shrimp, it is essential to know the lowest temperature to which they remain physiologically active but require minimum oxygen and stop movement of body and appendages. This can be done artificially by lowering temperature, thus forcing shrimp to temporary hibernation and facilitating its transport in Uve condition. It is also vital to know how many shrimp return to normal after cold treatment and the lowest temperature beyond which no shrimp will regain consciousness even if the temperature is raised, i.e. the point of no return. This study deals with determination of point of no return for post larvae, juvenile and market sized Penaeus monodon and juvenile Pendeus indicus. No information is available on this subject.